Analisa Daya Beli Masyarakat Terhadap Tingkat Inflasi Barang dan Pertumbuhan Ekonomo Mikro - Rien, Jairin Abdullah Jairin (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2024)
This study aims to analyze the influence of people's purchasing power on the rate of inflation of goods and microeconomic growth. People's purchasing power reflects the ability of consumers to buy goods and services, which is influenced by income, prices of goods, and macroeconomic conditions. Inflation, which indicates a general increase in the price of goods and services continuously, can reduce people's purchasing power, especially in the microeconomic sector where most small and medium-sized businesses operate. In the context of microeconomics, changes in purchasing power have direct implications for the demand for goods and services. When inflation increases, prices of goods and services tend to increase, so that people's purchasing power decreases. This decline can cause a decrease in demand for small and medium-sized enterprise (SME) products, which in turn affects microeconomic growth. Conversely, when people's purchasing power increases due to price stability or increased income, the microeconomic sector can experience increased growth due to greater demand for goods and services. This study uses a quantitative method with secondary data taken from official institutions such as the Central Statistics Agency (BPS) and Bank Indonesia. The results of the study show a negative relationship between inflation and people's purchasing power, as well as a significant influence of purchasing power on microeconomic growth. To reduce the negative impact of inflation, there needs to be a proactive government policy in maintaining price stability and supporting people's purchasing power, especially in supporting the growth of the microeconomic sector.